“Nationalists, liberals, democrats”. Alfonso de Laferrère and the journal Política (1923-1924) (Quinto Sol, 2018)
In June 1923 Política hit the streets of Buenos Aires. The journal, opposed to the Radical administration and with “renovating” aims, was run by two young men with literary interests and a long-standing Demo-progressive partisanship: Alfonso de Laferrère and Julio Noé. The ties with the DPP did not end there, as this publication featured pieces from notable partycharacters such as Carlos Ibarguren and Lisandro de la Torre. This noteworthy contributors did not stop the demise of this endeavor, which took place less than a year later. Its defiance of the “Alvearist truce” and its critique of the Argentinean political system, close to Liberalism andReformism, were mostly forgotten. Nonetheless, authors related to rightwing Nationalism exalted Política as a harbinger of the “new ideas”. Was this journal a Demo-progressive publication, or was it a forerunner of La Nueva República? To answer this and other questions, this article will explore the short life of Política paying close attention and to the reception of European right-wing ideas. Following the “orthodox Maurrasian” Laferrère, this essay will scrutinize the links and tensions between Liberal, Democratic and Nationalist discourses in the early 1920s.
Keywords: Política; progressive democrat; nationalism; Laferrere; Maurras